2012
DOI: 10.1007/s00454-012-9464-y
|View full text |Cite
|
Sign up to set email alerts
|

A Center Transversal Theorem for Hyperplanes and Applications to Graph Drawing

Abstract: Motivated by an open problem from graph drawing, we study several partitioning problems for line and hyperplane arrangements. We prove a ham-sandwich cut theorem: given two sets of n lines in R 2 , there is a line such that in both line sets, for both halfplanes delimited by , there are √ n lines which pairwise intersect in that halfplane, and this bound is tight; a centerpoint theorem: for any set of n lines there is a point such that for any halfplane containing that point there are n/3 of the lines which pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…We also note that a similar result was established by Dujmović and Langerman (see Theorem 6 in [6]).…”
Section: Discussionsupporting
confidence: 85%
“…We also note that a similar result was established by Dujmović and Langerman (see Theorem 6 in [6]).…”
Section: Discussionsupporting
confidence: 85%
“…The main difference is that we use the result of Fox et al [8] instead of the Ham-Sandwich Theorem. We also note that a similar result was established by Dujmović and Langerman (see Theorem 6 in [6]).…”
Section: Discussionsupporting
confidence: 85%
“…Dujmović and Langerman [11] used the existence of OSH d (n) to prove a ham-sandwich cut theorem for hyperplanes. Matoušek and Welzl [21] observed that OSH 2 (n) = (n − 1) 2 + 1 and Eliáš and Matoušek [12] noticed that, for d ≥ 3, OSH d (n) ≤ twr d (cn) follows from Ramsey's theorem, where c depends on d. In Section 4, we prove the following result which again improves the upper bound by one exponential.…”
Section: Introductionmentioning
confidence: 99%